The Influence of Job Characteristics and Perceived Fairness Toward Psychological Empowerment Among Employees in PT Perusahaan Listrik Negara, Indonesia - Ika, Desvitasari (2012)
State-Owned Enterprises play a central role in the national economy. As they have moved towards a more global and competitive environment, in order to be successful in sustaining the competitive advantages in providing service to customer, employees play an important role in contributing to the success of organization. Therefore, organization should be able to increase motivation of its employees. Empowerment brings benefits to both employees and organizations. Employees offer advantages to contemporary organizations wanting to gain competitive advantage through adaptability, rapid response and innovation. However, this creates new challenges to organization to redesign the work and to consider the fairness determinants in order to successfully empowered employees. Thus,the purpose of this research is to examine the influence ofjob characteristics and perceived fairness toward psychological empowerment among employees in PT Perusahaan Listrik Negara (PLN), Indonesia. This research is conducted based on quantitative method and questionnaire was established as the data collection tool based on several instruments adopted from previous research. Simple and multiple regression analysis were used to analyze the correlation as well as the influence of job characteristics and perceived fairness as independent variables toward psychological empowerment as dependent variable. This research found considerable evidence about the influence of job characteristics and perceived fairness toward psychological empowerment. Furthermore, this research has a high expectation on the study of empowering employees in Indonesia perspective to provide more knowledge and suggestions contribute to the Indonesian State-Owned Enterprises sector development as a foundation to be succeeded in facing more competitive business environment.